Politics and Parenthood: An Examination of UK Party Leadership Elections. Issue 1 (27th June 2017) - Smith, Jessica C
Abstract: As women increasingly campaign for the highest political offices, this original content analysis study examines the extent to which gender and parenthood play a role in political leadership using British political party leadership elections as a case study. Competing hypotheses from the limited literature on politics and parenthood are examined. The article finds that family mentions have varied over time and contrary to some gender literature men's family was at times of greater interest than women's. Evidence is found for the politicisation of motherhood and a possible 'maternal mandate'. In parallel, fatherhood was of increasing interest and the rise of the modern man can be seen. Yet, male candidates appear to have an 'opt-out clause' in any politicisation of fatherhood. Further questions about politics and parenthood begged by this article open future research avenues.